The control techniques drives and controls handbook - Drury, Bill (Institution of Engineering and Technology, 2009)
This book contains a great deal of practical information for drives and industrial engineers who use motors and drives. It is a comprehensive guide to the technology underlying drives and motors. It contains sufficient theory to give both user and student an insight into the design of these components and thereby the constraints and opportunities that exist. It has been radically revised and expanded from the previous edition to contain much new information.
Previous edition: 2001.
Keywords: Electric controllers.; Electric driving.; elektronické knihy; electronic books